Sclerostin as a biomarker of physical exercise in osteoporosis: A narrative review - Oniszczuk, Anna; Kaczmarek, Agnieszka; Kaczmarek, Mateusz; Ciałowicz, Maria; Arslan, Ersan; Silva, Ana Filipa; Clemente, Filipe Manuel; Murawska-Ciałowicz, Eugenia (Frontiers in Endocrinology, 2022)
Osteoporosis, a disease of low bone mass, is characterized by reduced bone mineral density (BMD) through abnormalities in the microarchitecture of bone tissue. It affects both the social and economic areas, therefore it has been considered a lifestyle disease for many years. Bone tissue is a dynamic structure exhibiting sensitivity to various stimuli, including mechanical ones, which are a regulator of tissue sclerostin levels. Sclerostin is a protein involved in bone remodeling, showing an anti-anabolic effect on bone density. Moderate to vigorous physical activity inhibits secretion of this protein and promotes increased bone mineral density. Appropriate exercise has been shown to have an osteogenic effect. The effectiveness of osteogenic training depends on the type, intensity, regularity and frequency of exercise and the number of body parts involved. The greatest osteogenic activity is demonstrated by exercises affecting bone with high ground reaction forces (GRF) and high forces exerted by contracting muscles (JFR). The purpose of this study was to review the literature for the effects of various forms of exercise on sclerostin secretion.